Interjurisdictional Sorting and Majority Rule: An Empirical Analysis - Epple, Dennis; Romer, Thomas; Sieg, Holger (Econometrica, 2001)
The goal of this paper is to provide a comprehensive empirical analysis of majority rule and Tiebout sorting within a system of local jurisdictions. The idea behind the estimation procedure is to investigate whether observed levels of public expenditures satisfy necessary conditions implied by majority rule in a general equilibrium model of residential choice. The estimator controls for observed and unobserved heterogeneity among households, observed and unobserved characteristics of communities, and the potential endogeneity of prices and expenditures, as well as the self-selection of households into communities of their choice. We estimate the structural parameters of the model using data from the Boston Metropolitan Area. The empirical findings reject myopic voting models. More sophisticated voting models based on utility-taking provide a potential explanation of the main empirical regularities.